Emotions, technology, and design - Tettegah, Sharon Y.; Noble, Safiya Umoja (Academic Press, an imprint of Elsevier, 2016)
Emotional design explicitly addresses the emotional relationship between the objects and the subjects of design-in this book, the objects are technologies, and the subjects are technology users. The first section delves into the philosophy and theory of emotional design to provide a foundation for the rest of the book, which goes on to discuss emotional design principles, the design and use of emoticons, and then intelligent agents in a variety of settings. A conclusion chapter covers future research and directions. Emotions, Technology, and Design provides a thorough look at how technology design affects emotions and how to use that understanding to in practical applications
Includes bibliographical references and index
Keywords: COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Emotions; Human-computer interaction; Technology / Psychological aspects; Informatik; Psychologie; Technology -- Psychological aspects